Fracture Risk Assessment in Atypical Parkinsonian Syndromes. Issue 3 (31st January 2021) - Kobylecki, Christopher; Glasse, Hannah; Amin, Jigisha; Gregson, Celia L.; Lyell, Veronica; Henderson, Emily J.
ABSTRACT: Background: Bone health and fracture risk reduction are increasingly recognized as important issues in Parkinson's disease (PD). However, the evidence for fracture risk management in atypical parkinsonism (AP) is less clear. Guidance on management of bone health in PD has recently been published. Objectives: To evaluate the outcome of fracture risk assessment in a cohort of patients with AP, compared to a population with idiopathic PD. Methods: We did a cross‐sectional study of patients with PD or AP who had fracture risk assessed at two tertiary movement disorder centres. Data on fracture risk as assessed using QFracture and FRAX were collected. To assess for the effect of age on fracture risk we compared the risks of PD and AP patients aged ≤70 and >70 years. Results: We assessed 71 patients with AP and 267 with PD. Age, sex and body mass index were similar between groups; patients with AP were more likely to have fallen in the previous year. Major osteoporotic fracture risk was greater in patients with AP aged ≤70 compared to PD; no differences between groups were seen in those aged >70 years. 76% of those with AP, and 63% with PD, had an estimated fracture risk indicating bone‐sparing treatment, but only 33% of patients with AP were receiving this where it was indicated. Conclusion: There is scope for considerable improvement in fracture risk assessment and treatment in atypical parkinsonism, taking into account the worse prognosis of this patient group.